Is seasonal flowering time of Paphiopedilum species caused by differences in initial time of floral bud differentiation?. Issue 5 (20th August 2021) - Feng, Jing-Qiu; Xia, Qian; Zhang, Feng-Ping; Wang, Ji-Hua; Zhang, Shi-Bao
Abstract: Members of the genus Paphiopedilum are world-famous for their large, colourful flowers, unique floral morphology and long floral lifespan. Most Paphiopedilum species bloom in spring or autumn. The control of flowering time is of great significance to the commercial production of floral crops, because it affects the sales and prices of flowers. However, the mechanism that regulates when Paphiopedilum species bloom is unclear. In the present study, floral bud initiation and development of P. micranthum (spring-flowering species with one flower per stalk), P. dianthum (autumn-flowering species with multiple flowers per stalk) and P. henryanum (autumn-flowering species with one flower per stalk) were investigated by morphological and anatomical methods. We divided Paphiopedilum floral bud differentiation into six phases: the initiation of differentiation, inflorescence primordium differentiation, flower primordium differentiation, sepal primordium differentiation, petal primordium differentiation and column primordium differentiation. We found that the timing of floral bud differentiation for the three species was synchronized when experiencing the same environment, while the period from initiation to flowering largely differed. In addition, initiation of floral bud differentiation in P. dianthum was earlier at a warmer environment. The difference in flowering time of three species was mainly caused by the duration of floral bud development, rather than the initiation time. The findings were of great significance for the cultivation and flowering regulation of Paphiopedilum species. Abstract : Members of the genus Paphiopedilum are world-famous for their unique and delicate flowers. Most Paphiopedilum species bloom in spring or autumn, while the mechanism that regulates when Paphiopedilum species bloom is unclear. In this study, we found that the difference in flowering of P. dianthum (autumn-flowering), P. micranthum (spring-flowering) and P. henryanum (autumn-flowering) was mainly caused by the duration of floral bud development, rather than the initiation time. In addition, initiation of floral bud differentiation in P. dianthum was earlier in warmer environments. The findings are of great significance for the cultivation and flowering regulation of Paphiopedilum species.